Joint Remote Laser Induced Breakdown Spectroscopy and Raman Laser Spectroscopy for Investigation of Planetary Geochemical Composition - Mahider Kebede (ASTU, 2024)
This thesis focuses on combining Raman spectroscopy and LIBS for planetary geochemical investigations, specifically targeting minerals commonly found in extraterrestrial environments: chalcanthite, calcite, halite, olivine, gypsum, nontronite, and quartz. Spectral datasets for these minerals were obtained from the Raman Raman User Friendly Field Frequency (RRUFF) database, and the elemental Compositions of minerals such as CuSO₄•5H₂O, CaCO₃, NaCl, Fe₂SiO₄, Mg₂SiO₄, CaSO₄•2H₂O, Na₀.₃Fe³⁺₂(Si,Al)₄O₁₀ (OH)₂•nH₂O and SiO₂ were sourced from the National Institute of Standards and Technology (NIST) database and imported into Origin software. After preprocessing steps in Origin, including baseline correction and noise reduction, the spectral data were combined using fusion. When combined, these techniques provide complementary data, raising the question of how to optimize their use to maximize scientific output. To address this question, we conducted a study in which we investigated LIBS and Raman data, their mixtures, multivariate data analysis (MVA) techniques and specifically principal component analysis (PCA) to assess the potential of identifying targeting minerals commonly found in extraterrestrial environments using LIBS and Raman data alone, as well as their fused data. Our findings indicate that data fusion of LIBS and Raman spectroscopy enhanced the detection capabilities compared to individual techniques, this fusion approach reveals new aspects that would remain hidden if the data were not integrated, highlighting the benefits of a combined analysis.
Keywords: Raman spectroscopy, LIBS, planetary geochemical, data fusion